The effect of oil heat treatment on color changes and preference of sengon (Falcataria moluccana) and African tulip (Spathodea campanulata) woods - Al Qorny, Faiz; Suri, Intan Fajar; Febryano, Indra Gumay; Hidayat, Wahyu (Global Forest Journal., 2026)
Indonesia faces increasing pressure on its natural forest resources due to deforestation and rising demand for wood, encouraging the utilization of fast-growing species such as sengon (Falcataria moluccana) and underutilized invasive species such as African tulip (Spathodea campanulata). However, both species are characterized by naturally light surface colors, which are often perceived as less attractive for decorative and interior applications. Oil heat treatment (OHT) has been used to modify wood color and enhance visual appearance. This study evaluated the effects of OHT at 160°C, 180°C, 200°C, and 220°C for 2 hours on color changes and public color preferences of sengon and African tulip woods. Color changes were visually observed and quantitatively analyzed using the CIE-LAB color system, while preference data were collected through an online survey involving male and female respondents. The results showed that OHT caused significant darkening of wood surfaces, with African tulipwood exhibiting greater color changes than sengon. Preference analysis indicated that female respondents tended to favor wood colors heat-treated at moderate temperatures (180°C), whereas male respondents preferred darker colors produced at higher temperatures (200–220°C). For African tulip wood, treatment at 200°C was the most preferred overall by both genders. These findings demonstrate that oil heat treatment effectively modifies wood color and that consumer color preferences vary by gender, which may be considered in visually oriented wood applications.